Internet Marketing Strategy Demandailing Café in Building a Digital Brand on Instagram - Rifkya Xena Aminullah JR; Jokhanan Kristiyono (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
This study raises the marketing communication strategy carried out by the Demandailing management in building the Demandailing Cafe brand image. This study describes the digital marketing strategy carried out by Demandailing Café in building a brand image on Instagram social media to the public, especially Demandailing Cafe consumers located in Surabaya. The benefits obtained from this research are as an academic reference on digital marketing in building a practical brand image on Instagram social media. The research method used in this research is descriptive qualitative, with an analysis of Integrated Marketing Communication (IMC) and digital marketing. Data was collected through in-depth interviews, observation, and documentation studies. This study concludes that in carrying out the Demandailing digital marketing strategy to build a brand image on Instagram social media, it is determined by how the products offered are highlighted in terms of the promotional content of the Demandailing Café product itself. Submission of the brand image itself indirectly becomes an interpersonal communication from Demandailing with customers who see Instagram. Demandailing always makes innovations in building a brand image that is not done by other cafe entrepreneurs, both in terms of soft selling and hard selling.